Psychological Approach in Personality Development of Theodore Decker’s Character in “The Goldfinch” - Ayu Bandu Retnomurti; Nurmala Hendrawaty (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2022)
The research aims to describe the personality and the personality development of Theodore Decker through psychosocial development perspectives in the main character of The Goldfinch novel. His personality becomes an example of how family and social environment contribute to the development of one’s personality. The research method used in understanding and in analysing the novel was descriptive qualitative. The research results are: According to Erik Erikson’s eight stages in psychosocial development theory, Theo has passed four major stages they are the stages of initiative vs guilt (14%), industry vs inferiority (14%), identity vs role confusion (46%), and intimacy vs isolation (29%). Theo struggles to pass the stage of identity vs role confusion. It has led him to the situation where he faces difficulties on understanding his identity and role within society. Theo is grown up as a person with less empathy for others, struggles with his drug addiction, and has trouble making commitments; Erik Erikson’s psychosocial development of the personality emphasizes the social influences in the development of the ego. Erikson’s theory of psychosocial development has eight distinct stages. Completing each step results in a healthy personality and the acquisition of the ego to resolve subsequent crises. Conversely, failure to complete a set will lead to ability reduction in completing further stages and an unhealthier personality and sense of self. Instead of focusing on sexual development, this theory is interesting in how children socialize and how social environment affects their senses.